The African Charter on Democracy, Election and Governance and Constitutionalism in Nigeria - Baba Isaac Ibrahim (International Studies Journal)
The practice of democracy in Nigeria has been rippled with many challenges especially, the lack of democratic culture largely due to long military rule before the year 1999. It is against this background, that this article discusses the African Charter on Democracy, Election and Governance (ACDEG) and Constitutionalism in Nigeria by examining the practice of democracy in Nigeria vis-à-vis the electoral processes and governance in Nigeria. Historical methodology was adopted in this study relying on primary and secondary sources of data. From the study, there is need for the establishment of viable democratic structures in Nigeria anchored on constitutionalism in line with the provisions of the ACDEG. The article therefore, submits that the ACDEG should not only be made justifiable but a mechanism for monitoring compliance among African nations be put in place like the case of African Peer Review Mechanism (APRM) in the implementation of the New Partnership for Africa's Development (NEPAD) initiative. There should be a mechanism for monitoring, evaluation and enforcement of the ACDEG in Nigeria in order to realize the objectives of the ACDEG.